Transcranial Direct Current Stimulation Ameliorates Cognitive Impairment via Modulating Oxidative Stress, Inflammation, and Autophagy in a Rat Model of Vascular Dementia - Guo, Tao; Fang, Jia; Tong, Zhong Y.; He, Shasha; Luo, Yingying (Frontiers in Neuroscience, 2020)
To investigate the potential applications and the molecular mechanisms of transcranial direct current stimulation (tDCS) on cognitive impairment in a vascular dementia (VD) animal model. Sprague-Dawley rats were used in this study. VD rat model was induced by modified permanent bilateral common carotid artery occlusion (2-VO) approach. Anodal tDCS was applied to the animals. Morris water maze was used to analyze spatial memory and navigation ability. The pathological changes in the hippocampal CA1 region and cerebral cortex were examined via Hematoxylin-Eosin staining. The rats were sacrificed for the measurement of the level of superoxide (SOD), glutathione (GSH), reactive oxidative species (ROS), malondialdehyd (MDA), Interleukin (IL)-1β, IL-6 and tumor necrosis factor (TNF)-α level in the hippocampus. Western blot was carried out to measure the hippocampal expression of microtubule-associated protein 1 light chain 3 (LC-3) and p62. Rats with VD have decreased number of neurons in the hippocampus and cerebral cortex, as well as worse cognitive impairment. The proliferation of activated microglia and astroglia, accompanied with attenuation of myelination were observed in the white matter about 1 month after 2-VO operation. These abnormalities were significantly ameliorated by tDCS treatment. Further study revealed that anodal tDCS could suppress the MDA and ROS level, while enhance the SOD and GSH level to reduce the oxidative stress. Anodal tDCS could inhibit hypoperfusion-induced IL-1β, IL-6 and TNF-α expression to attenuate inflammatory response in hippocampus. Moreover, anodal tDCS treatment could alleviate autophagy level. The study has demonstrated a possible therapeutic role of tDCS in the treatment of cognitive impairment in VD.